2017
DOI: 10.1111/mec.14028
|View full text |Cite
|
Sign up to set email alerts
|

Rapid genetic and morphologic divergence between captive and wild populations of the endangered Leon Springs pupfish, Cyprinodon bovinus

Abstract: The Leon Springs pupfish (Cyprinodon bovinus) is an endangered species currently restricted to a single desert spring and a separate captive habitat in southwestern North America. Following establishment of the captive population from wild stock in 1976, the wild population has undergone natural population size fluctuations, intentional culling to purge genetic contamination from an invasive congener (Cyprinodon variegatus) and augmentation/replacement of wild fish from the captive stock. A severe population d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 86 publications
2
20
0
1
Order By: Relevance
“…Most notably, in both DYS and MDP, the dramatic decline or extinction of the two communities occurred after the resident hybrid populations were removed and replaced with individuals from SNARRC (Echelle et al, ). It is possible that individuals from this long‐standing captive community had difficulty making the transition back to the natural habitat (Black et al, ). This suggests that past instability after reintroducing C. bovinus from SNARRC is likely to have been caused by genetic divergence between the captive and wild populations (Black et al, ), and not the result of maladaptive social behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most notably, in both DYS and MDP, the dramatic decline or extinction of the two communities occurred after the resident hybrid populations were removed and replaced with individuals from SNARRC (Echelle et al, ). It is possible that individuals from this long‐standing captive community had difficulty making the transition back to the natural habitat (Black et al, ). This suggests that past instability after reintroducing C. bovinus from SNARRC is likely to have been caused by genetic divergence between the captive and wild populations (Black et al, ), and not the result of maladaptive social behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…The 2 months of monitoring before the 2013 extinction of the reintroduced C. bovinus from SNARRC suggested that additional habitat renovations were required in order to make the renovated shallow breeding areas less likely to disappear through water loss. However, Black, Seears, Hollenbeck, and Samollow () found that after approximately 15 years of isolation, C. bovinus from SNARRC had greater genetic diversity in heterozygosity and allelic richness, and they exhibited genetic and morphological divergence from those at DYS, perhaps indicating that habitat changes in MDP were not the sole cause for this most recent extinction. For example, the two populations differed in the frequency of genetic loci, suggesting that local adaptation had occurred, and fish from SNARRC varied from those at DYS in pectoral fin attachment sites and in the orientation of their heads, which could potentially affect their swimming ability and foraging behaviour, respectively (Black et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To estimate the influence of the m and M values on RAD tag fragment recovery, we determined the number of reconstructed fragments, their mean coverage and the proportion of polymorphic fragments for each value of M and m tested. We also evaluated the impact of these parameters on population genetics results by performing, for all m and M values, some of the most commonly used analyses using ddRADseq data (Capblancq et al, 2015; Kjeldsen et al, 2016; Black et al, 2017; Nunziata et al, 2017; Settepani et al, 2017; Elleouet & Aitken, 2018; Sherpa, Rioux, Pougnet-Lagarde, et al, 2018), i.e. mean individual heterozygosity, F ST among populations (estimated with the adegenet R package (Jombart, 2008)), Principal Component Analysis (PCA, using the adegenet R package (Jombart, 2008)), genetic structure with sNMF (using the LEA R package (Frichot & François, 2015)) and evolutionary history reconstruction using Approximate Bayesian Computation (performed with the diyABC program (Cornuet et al, 2014)).…”
Section: Methodsmentioning
confidence: 99%
“…Among these, double-digest RADseq, or ddRADseq (Peterson et al, 2012), is highly customizable as regards the final number of loci, depending on the choice of enzymes and range of fragment size selected. The ddRADseq approach has been applied with success to many purposes including population genetic studies (Kjeldsen et al, 2016; Black, Seears, Hollenbeck, & Samollow, 2017; Sherpa, Rioux, Goindin, et al, 2018), phylogenetic reconstructions (DaCosta & Sorenson, 2016; Vargas, Ortiz, & Simpson, 2017; Boubli et al, 2018; Lee et al, 2018; Sherpa, Rioux, Pougnet-Lagarde, & Després, 2018), demographic inferences (Capblancq, Després, Rioux, & Mavárez, 2015; Nunziata, Lance, Scott, Lemmon, & Weisrock, 2017; Settepani et al, 2017; Elleouet & Aitken, 2018) and landscape genetic analyses (Saenz-Agudelo et al, 2015; Johnson, Gaddis, Cairns, Konganti, & Krutovsky, 2017). Despite the recognized advantages of the ddRADseq technique, several limitations and weaknesses arose in the literature (Davey et al, 2013; K. R. Andrews et al, 2016; Lowry et al, 2017).…”
Section: Introductionmentioning
confidence: 99%